2013
DOI: 10.1371/journal.pone.0068631
|View full text |Cite
|
Sign up to set email alerts
|

Rupatadine Protects against Pulmonary Fibrosis by Attenuating PAF-Mediated Senescence in Rodents

Abstract: A similar immune response is implicated in the pathogenesis of pulmonary fibrosis and allergic disorders. We investigated the potential therapeutic efficacy and mechanism of rupatadine, a dual antagonist of histamine and platelet-activation factor (PAF), in bleomycin- (BLM-) and silica-induced pulmonary fibrosis. The indicated dosages of rupatadine were administered in rodents with bleomycin or silica-induced pulmonary fibrosis. The tissue injury, fibrosis, inflammatory cells and cytokines, and lung function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…Rupatadine, an antihistamine and inhibitor of PAF, has been shown to attenuate experimental lung fibrosis and improve lung function and survival, as well as reduce cellular senescence 135 . Rupatadine reduces the expression of CCAAT/enhancer-binding protein-β (C/EBPβ), IL-6, CXCL2 and other SASP factors 135 . These studies 135 also suggest that rupatadine decreases p53-dependent senescence in bleomycin-injured lung tissues.…”
mentioning
confidence: 99%
“…Rupatadine, an antihistamine and inhibitor of PAF, has been shown to attenuate experimental lung fibrosis and improve lung function and survival, as well as reduce cellular senescence 135 . Rupatadine reduces the expression of CCAAT/enhancer-binding protein-β (C/EBPβ), IL-6, CXCL2 and other SASP factors 135 . These studies 135 also suggest that rupatadine decreases p53-dependent senescence in bleomycin-injured lung tissues.…”
mentioning
confidence: 99%
“…A mouse model of bleomycin-induced lung injury and inflammation showed that repeated injury was accompanied by a loss of normal tissue architecture, a persistent increase in collagen deposition, increased collagen synthesis and increased number of myofibroblasts [37]. The fibrotic change in lung inflammation was associated with reduced total lung capacity, increased dynamic resistance and decreased dynamic compliance [38]. Subsequent studies showed that a variety of inflammatory cytokines and chemokines including TGFβ, CXCL6, IL-1, IL-5, IL-6, IL-17 modulate collagen deposition and the fibrotic effects of lung inflammation [39][44].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-activating factor (PAF) is a SASP member that is secreted by senescent cells in lungs treated with bleomycin. Rupatadine, an antihistamine and inhibitor of PAF, has been shown to attenuate experimental lung fibrosis and improve lung function and survival, as well as reduce cellular senescence 135 . Rupatadine reduces the expression of CCAAT/enhancer-binding protein-β (C/EBPβ), IL-6, CXCL2 and other SASP factors 135 .…”
Section: Ageing Mechanisms and Novel Therapiesmentioning
confidence: 99%
“…Rupatadine, an antihistamine and inhibitor of PAF, has been shown to attenuate experimental lung fibrosis and improve lung function and survival, as well as reduce cellular senescence 135 . Rupatadine reduces the expression of CCAAT/enhancer-binding protein-β (C/EBPβ), IL-6, CXCL2 and other SASP factors 135 . These studies 135 also suggest that rupatadine decreases p53-dependent senescence in bleomycin-injured lung tissues.…”
Section: Ageing Mechanisms and Novel Therapiesmentioning
confidence: 99%
See 1 more Smart Citation